2018
DOI: 10.1007/s12223-018-0590-7
|View full text |Cite
|
Sign up to set email alerts
|

The first isolation of Westerdykella dispersa in a critically burned patient

Abstract: Patients with critical thermal trauma belong to one of the most high-risk groups for development of infectious complications. Fungal infections are not among frequent complications during therapy of patients with thermal trauma, yet their incidence dramatically aggravates the prognosis for patients with this disorder. In the case report, we present the case of a young man with a critical burn, where Westerdykella dispersa was isolated. Identification of the pathogen was provided with a combination of cultivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…46 Two cases of human infections have been reported until now. 47,48 Sue et al reported the infection in a neutropenic patient with acute lymphoblastic leukemia. 48 Infectious complication around a peripherally inserted central catheter occurred.…”
Section: Scopulariopsis (Microascus) Sppmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Two cases of human infections have been reported until now. 47,48 Sue et al reported the infection in a neutropenic patient with acute lymphoblastic leukemia. 48 Infectious complication around a peripherally inserted central catheter occurred.…”
Section: Scopulariopsis (Microascus) Sppmentioning
confidence: 99%
“…The second case was isolated from a critically burned patient. 47 Three other isolates were recovered from lower extremity wounds or tissue in the United States identified as Westerdykella, one of them as W. dispersa and the other two as W. reniformis. 48 However, their virulence in these cases has not been acknowledged.…”
Section: Scopulariopsis (Microascus) Sppmentioning
confidence: 99%
“…Among them, 28 case series and 15 irrelevant studies were excluded. Finally, 36 case reports encompassing 44 burn patients were included for the final analysis 10–45 …”
Section: Resultsmentioning
confidence: 99%
“…In 36 of the 44 cases, fungal infections were initially suspected and identified from the burn wound samples 10–27,31–33,35–37,39–45 . In the remaining 8 cases, presentations of fungal wound infection were not observed, whereas invasive fungal infections were found in other sites such as blood, arterial thrombosis, teeth, feces, urine, sputum, and tracheal fluid 28–30,34,38 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation